A Cell Fate Switch in the Caenorhabditis elegans Seam Cell Lineage Occurs Through Modulation of the Wnt Asymmetry Pathway in Response to Temperature Increase. Issue 4 (1st April 2020) - Hintze, Mark; Koneru, Sneha L; Gilbert, Sophie P R; Katsanos, Dimitris; Lambert, Julien; Barkoulas, Michalis
Abstract: Developmental phenotypes are often consistent across individuals within a population in the face of environmental and genetic challenges. However, these challenges can exceed the level of system robustness and change developmental... Populations often display consistent developmental phenotypes across individuals despite inevitable biological stochasticity. Nevertheless, developmental robustness has limits, and systems can fail upon change in the environment or the genetic background. We use here the seam cells, a population of epidermal stem cells in Caenorhabditis elegans, to study the influence of temperature change and genetic variation on cell fate. Seam cell development has mostly been studied so far in the laboratory reference strain (N2), grown at 20° temperature. We demonstrate that an increase in culture temperature to 25° introduces variability in the wild-type seam cell lineage, with a proportion of animals showing an increase in seam cell number. We map this increase to lineage-specific symmetrization events of normally asymmetric cell divisions at the fourth larval stage, leading to the retention of seam cell fate in both daughter cells. Using genetics and single-molecule imaging, we demonstrate that this symmetrization occurs via changes in the Wnt asymmetry pathway, leading to aberrant Wnt target activation in anterior cell daughters. We find that intrinsic differences in the Wnt asymmetry pathway already exist between seam cells at 20° and this may sensitize cells toward a cell fate switch at increased temperature. Finally, we demonstrate that wild isolates of C. elegans display variation in seam cell sensitivity to increased culture temperature, although their average seam cell number is comparable at 20°. Our results highlight how temperature can modulate cell fate decisions in an invertebrate model of stem cell patterning.